PENGARUH KARAKTERISTIK INTERNAL PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN BARANG KONSUMEN NON-PRIMER YANG TERDAFTAR DI BEI - Saprilina, Lailia Riska; Satyawan, Made Dudy (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
This research aims to examine the internal characteristics of companies reflected in Company Size, Board Size, Audit Committee Size, and Board Gender on Audit Delay. The sample consists of 82 companies observed from 2019 to 2022, with a total sample size of 328. Purposive sampling method was chosen by the researcher for this study. Hypothesis testing was conducted using multiple regression analysis with the assistance of SPSS version 29 software. The findings indicate that company size and audit committee size have a positive effect on audit delay, while board size has a negative effect on audit delay. However, the gender of the board of directors did not show a significant influence on audit delay